Effect of strain on the photocatalytic reaction of graphitic carbon nitride: insight from single-molecule localization microscopy - Chan, Jia Xin (2025)
Strain engineering in two-dimensional nanomaterials holds significant potential for modulating the lattice and band structure, particularly through localized strain, which enables modulation at specific regions. Despite the remarkable effects of local strain, the relationships among local strain, spatial correlation of photogenerated charge carriers, and photocatalytic performance remain elusive. The current study coupled single-molecule localization microscopy with coordinate-based colocalization (CBC) analysis to explain these relationships. The methodology involved mapping the spatial distributions of photoinduced oxidation and reduction reaction sites across graphitic carbon nitride (g-C3N4) nanosheets, quantifying and spatially resolving their spatial correlation, and also evaluating their photocatalytic activity. The study examined 65 individual g-C3N4 nanosheets, revealing interparticle and intraparticle heterogeneity, which was classified based on their CBC score distributions. Among the 65 g-C3N4 nanosheets, type A nanosheets predominated (45 out of 65) and demonstrated both correlated and noncorrelated subregions along some wrinkles. In contrast, type B nanosheets (20 out of 65) were primarily characterized by noncorrelated subregions with minimal correlated localizations. The coexistence of both noncorrelated and correlated subregions inferred the structure of the wrinkles as folding wrinkles, which have larger tensile-strained areas than rippling wrinkles. Folding wrinkles promote colocalization through the formation of type I band alignment at tensile-strained subregions. This band alignment also enhances photocatalytic activity through a funneling effect and improved light absorption, leading to higher specific activity in correlated subregions compared to noncorrelated ones. The role of strain-induced band alignment in modulating the spatial correlation of the photoredox reaction and the photocatalytic performance at the subregion level is highlighted.